1035325 Hubungan Pemberian ASI Eksklusif dengan Indeks Massa Tubuh Pada Ibu Menyusui - Yuni Kurniati (STIKes Budi Mulia Sriwijaya, 2019)
Abstract In order to reduce morbidity and mortality rates for children, the United Nations Childrens Fund (UNICEF) and the World Health Organization (WHO) recommend that children should only be breastfed for at least six months, and breastfeeding should continue until the child is two years old. Exclusive breastfeeding from infants aged 0 to 6 months without the provision of other formula milk will greatly assist the growth and development of the baby, anti-allergic, have immunoglobulin substances and especially have perfect nutrition. The purpose of this study was to determine the relationship of exclusive breastfeeding with Body Mass Index in Lactating Mothers in the working area of Palembang's AlangAlang Lebar Health Center. This study uses a correlation research method with cross sectional approach. The population in this study were all mothers who breastfed and had children aged 6-12 months in October 2019. This study was conducted in 2019. The sample in this study amounted to 45 respondents. This research was conducted in the working area of Palembang's Alang-Alang Lebar Health Center. This research instrument in the form of a questionnaire and scales as a measurement tool. Data analysis was performed by univariate and bivariate analysis using the ChiSquare test. The results showed no significant relationship between exclusive breastfeeding with Body Mass Index for breastfeeding mothers in the work area of Alang-Alang Lebar Health Center in 2019. This conclusion was obtained from the p value (0.065) greater than α (0.05). Keywords: Body mass index, exclusive breastfeeding